Nephroprotectivity of Coccinia indica leaves against gentamycin-induced nephrotoxicity using in vitro and in vivo models - Neelima Satrasala, Dwarakanadha Reddy Peram, Chandra Sekhar Kothapalli Bannoth (Journal of Applied Pharmaceutical Science, 2021)
The present study intends to explore the efficacy of ethanolic extract of Coccinia indica (EECI) leaves against nephrotoxicity induced by gentamycin (GT) via in vitro and in vivo experiments. Four groups with six Wistar rats each, with Group I receiving normal saline, Group II with GT (80 ml/kg), Groups III and IV with lower (200 mg/kg) and higher dose (400 mg/kg) of test drug, respectively, were deliberated for a 7-day experiment. Serum creatinine, urea, alanine transaminase, aspartate transaminase, and alkaline phosphatase were considered as biomarkers along with antioxidant enzymes to assess the nephroprotective nature of the extract and the results are supported by histograms. High-performance liquid chromatography analysis presented the phytochemicals present in the test drug. 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide assay showed the competence of the test extract for the nephroprotective nature. The biomarker levels increased and the antioxidant levels decreased significantly with the administration of GT than the control group. However, with a treatment of 200 mg/kg of the test drug, there were notable required alterations for all considered parameters, and with a higher dose, the levels of biomarkers and catalase, superoxide dismutase, and reduced glutathione were almost near to control ones indicating the nephroprotective nature of considered plant extract. The EECI leaves posed an optimistic effect toward GT-induced nephrotoxicity.
Keywords: Nephrotoxicity, gentamycin, Coccinia indica, antioxidants, HEK-293 cells.